Assess of Pediatric Oral Health-Related Quality in Children with Dental Injury - Zahra Abdullah Taha Alsafi,; Somayah Oqaibi,; Zohair Masood Alghamdi,; Somaya Abdulkarim Alghamdi,; Abdulah Ahmed Alghamdi,; Abdulmohsen Abdullah Hussain Aleithan,; Shooq Fahad Alamray,; Waad Naghi, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: Traumatic dental injuries (TDI) are a significant public health concern, especially among children , with notable implications for both oral health and quality of life. These injuries, commonly affecting primary dentition, can have physical, psychological, and social impacts. Despite this, few studies have evaluated the effects of TDI on the oral health-related quality of life (OHRQoL) of children, particularly in specialized dental trauma care programs. This study aims to assess the impact of TDI on OHRQoL among preschool children and their families and to evaluate the psychometric properties of the Early Childhood Oral Health Impact Scale (ECOHIS) for this population. Methods: A study was conducted at a Dental clinic ppl, involving children aged 2- 6 years with TDI. The sample included 146 children who met inclusion criteria from a total of 178 children with TDI. Data were collected through demographic questionnaires, TDI classification, and the version of the ECOHIS. Psychometric evaluations of the ECOHIS were performed, including reliability, test-retest, and construct validity assessments. Data analysis was conducted using SPSS, with statistical tests to compare the impact of uncomplicated versus complicated TDIs. Results: The study found that 54.1% of the participants were male, with a mean age of 4.31 years. Central incisors were the most frequently injured teeth. The majority (90%) of children sought treatment more than 24 hours after the injury. The psychometric evaluation of the ECOHIS showed good reliability (Cronbach’s α = 0.83) and test-retest reliability (ICC = 0.79). The overall ECOHIS score indicated a moderate negative impact on OHRQoL (mean score = 6.79). Complicated TDIs significantly worsened the OHRQoL, with higher scores on both the total scale and specific subscales, particularly in child symptoms and function domains. Conclusion: This study highlights the significant impact of TDI on the oral health- related quality of life of preschool children and their families, particularly when injuries are complicated. The ECOHIS demonstrated satisfactory reliability and validity for use in this population, offering a valuable tool for assessing the broader impacts of TDI in dental trauma care programs. These findings underscore the importance of timely treatment and the need for comprehensive care in improving the OHRQoL of children with dental injuries.